2018
DOI: 10.1039/c7ay02998e
|View full text |Cite
|
Sign up to set email alerts
|

Portable near infrared spectroscopy applied to abuse drugs and medicine analyses

Abstract: Near infrared (NIR) spectroscopy using a portable instrument (microNIR) associated with chemometrics models analysis was applied to quantify cocaine, and to classify synthetic drugs by their functional chemical composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…A considerable number of research articles and reviews have directed their attention to the potential of developing mobile and handheld devices based on various detection methods. Some of these include Raman [82][83][84][85][86][87], ultraviolet (UV) [88], visible [89], ultraviolet-visible (UV-vis) [90][91][92], near-infrared (NIR) [93,94], Fourier-transform infrared spectroscopy (FTIR) [95,96], induced fluorescence [97][98][99], electrochemical detectors (ECDs), and X-ray fluorescence [100][101][102]. The vast majority of these methods can be adapted to detect and quantify eluting analytes in an LC instrument.…”
Section: The Detectormentioning
confidence: 99%
“…A considerable number of research articles and reviews have directed their attention to the potential of developing mobile and handheld devices based on various detection methods. Some of these include Raman [82][83][84][85][86][87], ultraviolet (UV) [88], visible [89], ultraviolet-visible (UV-vis) [90][91][92], near-infrared (NIR) [93,94], Fourier-transform infrared spectroscopy (FTIR) [95,96], induced fluorescence [97][98][99], electrochemical detectors (ECDs), and X-ray fluorescence [100][101][102]. The vast majority of these methods can be adapted to detect and quantify eluting analytes in an LC instrument.…”
Section: The Detectormentioning
confidence: 99%
“…Since then, several studies have reported the use of benchtop and portable NIR and MIR instruments with multivariate calibration models (mostly PLS), taking into consideration calibration sets that are representative for the quantitative analysis of illicit drugs in tablets/powder, such as methylamphetamine, 174 heroin 175 and cocaine. [176][177][178][179][180] Pérez-Alfonso et al 181 used PLS regression to determine the content of cocaine impregnated in seized materials, within which were found other forms of illicit drugs. Measurements were made by ATR-FTIR and diffuse reflectance (DR) NIR directly from the surface of four different types of materials, white and black textiles, paper and foam.…”
Section: Infrared Spectroscopymentioning
confidence: 99%
“…The aforementioned techniques offered sensitivity, selectivity and precision yet they were time-consuming, destructive and required extensive sample preparation. On the contrary, spectroscopic techniques including Fourier transforminfrared (FTIR), near-infrared (NIR) and Raman spectroscopy have shown to be quicker, simpler and mobile (Faisall et al 2009;Assi et al 2011a;Assi et al 2011b;Caporaso et al 2018;Bouyé et al 2018;Correia et al 2018;Yang et al 2019;Fedchak 2014;Crocombe 2018;Gerace et al 2019). When combined with multivariate regression analysis, spectroscopic techniques offered rapid, on-spot and non-destructive quantification of APIs medicines (The Medicines Compendium Modafinil Provigil 100 mg Tablets 2020; Crocombe 2018).…”
Section: Introductionmentioning
confidence: 99%